PENGARUH PEMBERIAN LISIN DENGAN DOSIS YANG BERBEDA PADA PAKAN KOMERSIAL TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN GURAME (Osphronemus gouramy) - ADAM, AIN; Yuniarti Koniyo; Arafik Lamadi (Journal Of Fisheries Agribusiness, 2025)
Gourami (Osphronemus gouramy) is one of the most popular freshwater fish in Indonesia. This species has relatively slow growth, thus requiring improved nutritional quality in its feed. The lysine requirement for omnivorous fish is 2.07%, therefore lysine supplementation is necessary to meet their nutritional needs. The objective of this study was to determine the effect of lysine supplementation in commercial feed on the growth rate and survival rate of gourami fingerlings, as well as to identify the optimal lysine dosage. This research was conducted over a period of 30 days, from June to July 2025, at the Balai Benih Ikan Andalas Gorontalo (BBI). The experimental design used was a Completely Randomized Design (CRD) consisting of four treatments with three replications: control (A), lysine supplementation of 10 g/kg feed (B), 15 g/kg feed (C), and 20 g/kg feed (D). The feed used was commercial feed (PF 800) and lysine amino acid in the form of L-lysine HCL. The results showed that lysine supplementation in the feed had no significant effect on absolute length growth, absolute weight gain, or survival rate of gourami fingerlings. However, treatment C (15 g/kg feed) yielded the highest averages, with an absolute length of 0.34 cm, absolute weight of 0.75 g, and a survival rate of 87%. Water quality measurements during the rearing period showed an average temperature of 27°C, pH of 8, and dissolved oxygen of 7 mg/L, all within the normal range for gourami fingerlings.